Togo Mizrahi and the Making of Egyptian Cinema - Starr, Deborah A. (University of California Press, 2020)
In this book, Deborah A. Starr recuperates the work of Togo Mizrahi, a pioneer of Egyptian cinema. Mizrahi, an Egyptian Jew with Italian nationality, established himself as a prolific director of popular comedies and musicals in the 1930s and 1940s. As a studio owner and producer, Mizrahi promoted the idea that developing a local cinema industry was a project of national importance. Togo Mizrahi and the Making of Egyptian Cinema integrates film analysis with film history to tease out the cultural and political implications of Mizrahi's work. His movies, Starr argues, subvert dominant notions of race, gender, and nationality through their playful-and queer-use of masquerade and mistaken identity. Taken together, Mizrahi's films offer a hopeful vision of a pluralist Egypt. By reevaluating Mizrahi's contributions to Egyptian culture, Starr challenges readers to reconsider the debates over who is Egyptian and what constitutes national cinema.;"A captivating account of Egyptian film director Togo Mizrahi. Starr shows that Mizrahi's distinct, often comical vision of Egypt captured a dramatic moment of social, political, and cultural transformation in which people of diverse backgrounds coexisted and struggled to achieve better lives." JOEL GORDON, author of Revolutionary Melodrama: Popular Film and Civic Identity in Nasser's Egypt;"A remarkable study of a remarkable career. Starr offers a comprehensive analysis of a life in filmmaking that adds nuance to our definition of Egyptian nationalism and enhances our appreciation of Alexandrian cinema. This is a book of recovery, reclamation, and celebration." NANCY E. BERG, Professor of Hebrew and Comparative Literature, Washington University in St. Louis